Taiwan's Foreign Policy Strategy Through the New Southbound Policy in Strengthening Labor Relations with Indonesia - Muhammad Raditya Iskandarsyah; Moh. Fathoni Hakim (Journal of Governance and Social Policy, 2026)
Amidst diplomatic isolation resulting from the One China policy and a demographic crisis, Taiwan faces a dual burden that threatens its national resilience. Although Taiwan's labor cooperation has developed rapidly, existing literature remains dominated by macroeconomic analyses, leaving a gap regarding its role as a geopolitical instrument. This study aims to analyze the implementation of Taiwan's foreign policy through a functional approach to labor cooperation with Indonesia. Employing a descriptive qualitative method and Christopher Hill's Foreign Policy Strategy framework, this research examines the conversion of resources into operational capabilities. The findings indicate that through the New Southbound Policy (NSP), Taiwan strategically transforms its labor needs into a functional diplomatic instrument to expand its international presence. Semi-official institutions such as TETO and IETO function effectively as paradiplomatic infrastructures to manage asymmetric interdependence and build legitimacy. In conclusion, labor mobility has been transformed into a non-traditional geopolitical instrument, enabling Taiwan to maintain its relevance in Southeast Asia without relying on formal diplomatic channels.